Integration of design thinking and conceive-design- implement-operate within OBE framework in entrepreneurship course for civil engineering students / Che Maznah Mat Isa and Hamidah Mohd Saman. - Mat Isa, Che Maznah; Mohd Saman, Hamidah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
Design thinking (DT) is a robust framework for creatively identifying and solving various human problems. It offers a systematic solution to train engineering student's critical and creative thinking to solve complex engineering problems. The DT method can be integrated with the conceive-design-implement-operate (CDIO) framework to develop personal skills together with inter-personal skills. This paper presents the outcomes attained by the final year civil engineering students from Technology Entrepreneurship (ENT600) course. Teaching delivery method and assessment of outcomes are very important to determine students' performance with regards to this course. The course outcomes were assessed using various assessment tools such as case study, assignment/project, report and presentation. Two (2) groups of students from ENT600 course were selected as case studies to generate a comparison between their outcomes' attainment using two different learning methods; namely the traditional OBE and DT-CDIO integrated approach, respectively. The case studies used the data obtained from ENT600 course which is offered to final year undergraduates at the Faculty Civil Engineering, UiTM Shah Alam. This study highlights the importance in using DT method as an effective teaching and learning method to tackle complex problems systematically by understanding the human needs (empathize), re-framing and defining the problem in human- centric ways (define), creating many ideas (ideate), adopting a hands-on approach (prototype) and finally developing a prototype/solution to the problem (test). The coefficient variation indicates a significant difference between the two group outcomes' attainment for the course. Thus, this study shows the difference between the students' attainment using different learning methods used. The study revealed the assessment using DT-CDDIO approach as a possible transformation agent that is able to improve the delivery and course outcomes' attainment. Therefore, a modification on assessment methods based on DT approach is proposed as an accompanying method to evaluate the outcomes' attainment.